1983
DOI: 10.1002/art.1780260105
|View full text |Cite
|
Sign up to set email alerts
|

Anemia associated with rheumatoid disease

Abstract: Cell culture techniques were used to evaluate the number of erythroid colonies formed by circulating progenitor cells from 24 patients with rheumatoid disease and controls. A highly significant inverse correlation was demonstrated between erythroid colony counts and serum IgM and rheumatoid factor concentrations in the rheumatoid patients. The potential role of these factors in the pathogenesis of the anemia of rheumatoid disease is discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1986
1986
2015
2015

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…Cells derived from the bone marrow of RA patients showed less effective colony formation potency when compared to HC-derived bone marrow cells [191-193]. Further studies confirmed the reduced proliferative capacity of CD34+ HSC from RA patients [194-198].…”
Section: The Nine Hallmarks Of Aging and Ramentioning
confidence: 99%
“…Cells derived from the bone marrow of RA patients showed less effective colony formation potency when compared to HC-derived bone marrow cells [191-193]. Further studies confirmed the reduced proliferative capacity of CD34+ HSC from RA patients [194-198].…”
Section: The Nine Hallmarks Of Aging and Ramentioning
confidence: 99%